Catalog of the Chrysomelinae (Coleoptera: Chrysomelidae) deposited in the entomological collections of the Museu Paraense Emílio Goeldi (MPEG) and the Universidade do Estado do Pará (UEPA), Belém, Brazil - Sampaio, Aline; Viana, Jéssica Herzog; Fonseca, Claudio Ruy Vasconcelos Da (Zootaxa, 2024)
A comprehensive catalog is provided for most leaf beetles belonging to the Chrysomelinae subfamily, which are housed in the collections of two institutions in the state of Pará, located in northern Brazil: The Museu Paraense Emílio Goeldi (MPEG) and the Universidade do Estado do Pará (UEPA). The catalog includes detailed geographic distribution data for all species, along with new records and photographs (including two paratypes of Cryptostetha pereirai Bechyně, 1958, with descriptions of the aedeagus and spermatheca). Furthermore, information is provided on host plants, parasites, parasitoids, and predators associated with certain species.